The collected poems - Plath, Sylvia; Hughes, Ted, 1930-1998. (New York : HarperPerennial, 2008)
Contains, in sequence, all the poetry written by the author from 1956 until her suicide in 1963, together with fifty selections from her pre-1956 work.
Includes indexes.
Young Adult
Keywords: American poetry